1999
DOI: 10.1111/j.1574-695x.1999.tb01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the β2 toxin gene ofClostridium perfringensin diarrhoeic piglets in The Netherlands and Switzerland

Abstract: The two studies presented here were done to determine the prevalence of the K, L, O and enterotoxin genes and the novel L2 toxin gene of Clostridium perfringens in neonatal or pre-weaned piglets with diarrhoea or necrotic enteritis. All C. perfringens isolates were positive for the K and negative for the O and enterotoxin gene, implying that only non-enterotoxigenic type A and C strains were detected. The most important findings were the relatively high prevalence of the L2 toxin gene in isolates from diarrhoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For example, it was recently shown that over 100 lambs with clostridial dysentery, derived from different farms, all har‐boured C perfringens with at least one other toxin gene in addition to the a‐toxin gene cpa (Gkiourtzidis and others 2001). Furthermore, a recent study of diarrhoeic piglets revealed that strains of C perfringens containing only the a‐toxin gene were isolated much less often than strains which also contained one of the genes encoding the 13‐ or the 132‐toxin (Klaasen and others 1999). On the basis of these and several other observations, the authors consider that the a‐toxin by itself, although it may be needed as a basic virulence factor for successful infection, is probably not sufficient to cause severe intestinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was recently shown that over 100 lambs with clostridial dysentery, derived from different farms, all har‐boured C perfringens with at least one other toxin gene in addition to the a‐toxin gene cpa (Gkiourtzidis and others 2001). Furthermore, a recent study of diarrhoeic piglets revealed that strains of C perfringens containing only the a‐toxin gene were isolated much less often than strains which also contained one of the genes encoding the 13‐ or the 132‐toxin (Klaasen and others 1999). On the basis of these and several other observations, the authors consider that the a‐toxin by itself, although it may be needed as a basic virulence factor for successful infection, is probably not sufficient to cause severe intestinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Iota toxin causes inhibition of smooth muscle contraction and impairment of endocytosis, exocytosis and cytokinesis (Table 2). Only toxinotype E strains produce iota toxin and reported infections associated with iotatoxin are rare, but have been documented in cattle, horses, sheep, swine and rabbits (29,30,31,32,33). The LD 50 of iota toxin injected in mice intravenously was determined to be 40 µg/kg (19).…”
Section: Iota Toxin (Itx)mentioning
confidence: 99%
“…Recently, a variant of the -toxin known as 2 (cpb2 gene) has been associated with enteric diseases in a wide range of animals, including swine, cattle, poultry, sheep, horses and dogs (Klaasen et al, 1999;Garmory et al, 2000;Waters et al, 2005). Since its recognition as a separate toxin-producing strain, 2-toxigenic C. perfringens has also been isolated from various avian and aquatic species (Boujon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%